Baseline Retinal Examinations in Patients With Systemic Lupus Erythematosus Newly Initiating Hydroxychloroquine Treatment in a US Medicaid Systemic Lupus Erythematosus Population, 2000–2010. Issue 11 (26th October 2018) - Lin, Tzu‐Chieh; Marmor, Michael F.; Barbhaiya, Medha; Guan, Hongshu; Chen, Sarah K.; Feldman, Candace H.; Costenbader, Karen H.
Abstract : Objective: Baseline retinal examinations have long been recommended for patients beginning treatment with hydroxychloroquine (HCQ), but it is unknown how well this guideline is followed. We investigated baseline eye examinations among US SLE patients enrolled in Medicaid in whom HCQ treatment was newly initiated. Methods: Using billing codes, we identified SLE patients ages 18–65 years who were enrolled in Medicaid and residing in the 29 most populated US states, from 2000 to 2010. New users of HCQ were identified by filled prescriptions, with none filled in the preceding 12 months. Retinal examinations that were performed within 30 days before to 1 year after the index prescription were identified. We examined the proportions of patients receiving retinal examinations over the study years and compared the characteristics of those who did and those who did not receive examinations, using bivariable and multivariable logistic regression models. Results: Among 12, 755 SLE patients newly starting HCQ treatment, 32.5% received baseline dilated eye examinations. The proportions of patients receiving baseline eye examinations did not significantly change from 2000 to 2010 (31.0–34.4%; P for linear trend = 0.12). Factors associated with an increased likelihood of having an examination included female sex, Asian versus white race, and a higher number of laboratory tests performed during the preceding year. Compared with white patients, lower proportions of black and Native American patients with SLE had baseline retinal examinations. Conclusion: Only one‐third of patients with SLE enrolled in Medicaid and in whom HCQ was newly initiated received the recommended baseline retinal examinations, and this proportion did not significantly increase from 2000 to 2010. The sociodemographic variation in this recommended care has been observed for other recommended medical care in SLE and requires both further investigation and interventions to address it.